Recruitment and Retention of Healthy, Postmenopausal Women of African and European Ancestry: Results from a Dietary Intervention with Repeated Biospecimen Collections. Issue 3 (29th January 2022) - McCann, Susan E; Rodriguez, Elisa M; Erwin, Deborah; Yao, Song; Tritchler, David; Hullar, Meredith A J; O'Connor, Tracey; Lampe, Johanna W
ABSTRACT: Recruitment of minority participants to clinical trials, especially studies without therapeutic intent, has been historically challenging. This study describes barriers to and successes of recruitment and retention strategies to dietary studies. A flaxseed study was conducted in healthy, postmenopausal women of African ancestry (AA) and European ancestry (EA) to assess associations between gut microbial community composition and host metabolism (NCT01698294). To ensure equitable participation by AA and EA women, multiple forms of recruitment were utilized, including advertisements, posters, e-mail, word of mouth, and community outreach. Successful recruitment and retention of AA women to the intervention depended upon the specific methods used. AA women compared with EA women were more likely to respond to direct recruitment and community-based methods, rather than general advertisements. However, once women expressed interest, similar rates of consent were observed for AA and EA women (AA and EA: 51.6% vs. 55.7%, respectively; P  > 0.05), supporting the willingness of minority populations to participate in clinical research. Retention, however, was lower among AA compared with EA women (AA and EA: 57.6% vs. 80.9%, respectively; P  < 0.01), which may be related to multiple factors, including health reasons, intolerance to flaxseed, noncompliance with study requirements, time constraints, and nonspecified personal reasons. This study confirms the utility of direct community-based strategies for recruitment of diverse populations into nontherapeutic dietary intervention studies. The methods used successfully identified eligible women who expressed willingness to consent to the trial and were able to achieve >70% of recruitment goals for AA women. Future efforts are warranted to improve retention to complex studies. This trial was registered at www.clinicaltrials.gov as NCT01698294. Abstract : This report describes the experience and success at recruitment of a diverse study sample for a dietary intervention and shows that community engagement methods are effective for African-American women.